Increasing Life Expectancy and Pay-As-You-Go Pension Systems - Markus Knell (Oesterreichische Nationalbank (OeNB), 2012)
In this paper I study how PAYG pension systems of the notional defined contribution type can be designed such that they remain financially stable in the presence of increasing life expectancy. For this to happen two crucial parameters must be set in an appropriate way. First, the remaining life expectancy has to be based on a crosssection measure and, second, the notional interest rate has to include a correction for labor force increases that are only due to rises in the retirement age which are necessary to "neutralize" the increase in life expectancy. It is shown that the selfstabilization is effective for various patterns of retirement behavior and also – under certain assumptions – if life expectancy reaches an upper limit.
Keywords: H55; J1; J18; J26; 330; Pension System; Demographic Change; Financial Stability; Umlageverfahren; Alternde Bevölkerung; Sterblichkeit